2018
DOI: 10.1080/13697137.2017.1415321
|View full text |Cite
|
Sign up to set email alerts
|

The effect of programmed exercise over anxiety symptoms in midlife and older women: a meta-analysis of randomized controlled trials

Abstract: We aimed to perform a systematic review and meta-analysis in order to clarify the effect of programmed exercise over mild-to-moderate anxiety symptoms (ASs) in midlife and older women. A structured search of PubMed, Medline, Web of Science, Scopus, Embase, Cochrane Library, Scielo, and the US, UK and Australian Clinical Trials databases (from inception through July 27, 2017) was performed, with no language restriction using the following terms: 'anxiety', 'anxiety symptoms', 'exercise', 'physical activity', 'm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 56 publications
0
32
0
1
Order By: Relevance
“…Physical activity and PE are now considered as first-line interventions for the primary and secondary prevention and management of common chronic diseases [42][43][44][45]. Previous systematic reviews and meta-analyses of RCTs reported that PE might improve insulin sensitivity and reduce insomnia, depressive and anxiety symptoms in periand post-menopausal women [46][47][48][49]. However, the effect of PE on menopausal symptoms was insufficient to control for vasomotor symptoms in middle-aged women [50].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity and PE are now considered as first-line interventions for the primary and secondary prevention and management of common chronic diseases [42][43][44][45]. Previous systematic reviews and meta-analyses of RCTs reported that PE might improve insulin sensitivity and reduce insomnia, depressive and anxiety symptoms in periand post-menopausal women [46][47][48][49]. However, the effect of PE on menopausal symptoms was insufficient to control for vasomotor symptoms in middle-aged women [50].…”
Section: Discussionmentioning
confidence: 99%
“… 25 Another systematic review included a broader age range of mid-life and late-life (defined as 40 years and older) female participants, and identified 10 randomised controlled trials with 1463 participants for inclusion in meta-analysis. 24 The authors found that exercise interventions of 12–16 weeks’ duration were effective in reducing anxiety compared with control conditions with a similar effect size of −0.42; however, they found that interventions of 6–14 months’ duration were not effective. 24 …”
Section: Introductionmentioning
confidence: 97%
“…Two reviews addressed this question in relation to anxiety symptoms but specifically excluded those who had anxiety disorders. 24 , 25 One systematic review of exercise interventions for anxiety symptoms in older adults identified five randomised controlled trials, two cross-sectional studies and one cohort study, but the authors were unable to conduct a meta-analysis due to the methodological heterogeneity between studies. 25 Another systematic review included a broader age range of mid-life and late-life (defined as 40 years and older) female participants, and identified 10 randomised controlled trials with 1463 participants for inclusion in meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted about physical activity in people with severe mental ill-health. Systematic reviews suggest that physical activity is an effective treatment for depression [55,56], schizophrenia [57], and anxiety [58] and is associated with improved anthropometric measures, aerobic capacity, and quality of life among people with mental illness [56]. There is also good evidence that physical inactivity is predictive of a range of adverse health outcomes including obesity, diabetes and medical co-morbidity among people with severe mental disorders [59][60][61].…”
Section: Resultsmentioning
confidence: 99%